Pengembangan Asesmen Formatif Berbasis SLOA Pada Materi Statistika Kelas XI SMA - Faizza Zhara Adellia Adi; Chairil Faif Pasani; Rahmita Noorbaiti (JURNAL PENDIDIKAN, 2026)
Formative assessment practices in classrooms still focus on final outcomes and have not optimally encouraged students’ learning reflection. This study aimed to develop a valid, practical, and effective SLOA-based formative assessment on statistics of measures of central tendency for single data. The study employed the 4-D development model without the disseminate stage. The trial subjects consisted of 26 students of class XI-12 at SMAN 7 Banjarmasin. The developed product comprised four formative assessment packages in the form of essay questions equipped with self-assessment sheets, scoring rubrics, and answer keys. The results showed that the assessment was categorized as very valid with average scores of 3.57 and 3.75, very practical with 88%, and effective with an average completeness percentage of 88%.